The impact of street vending on financial perfomance of formal clothing retailers in Gweru. - Muzhangiri, Denny (Midlands State University, 2017)
This study seeks to find the impact of street vending on financial performance of formal clothing retailers in Gweru. This study draws inspiration from the gaps identified in previous research studies. Previous studies generalised the impact by actually looking at the impact of informal economy on business holistically. The main objective was to establish the relationship between street vending and financial performance of formal clothing retailers between the years 2013 and 2015. The other objectives were to determine the impact of street vending on customer count of formal retailers, to establish the relationship between street vending and conversion rate of formal retailers and to investigate the impact of street vending on average shopping cart of formal retailers. In order to establish the relationship, the study engaged in hypothesis testing. Main Sources used were four and included (Hudson et al 2012) who evaluated the impact of informal economy on businesses, Williams (2006) who analysed the relationship between small business and informal sector, (Chivivi et al 2014) who researched on advertising strategies and tactics used by flea market traders and (Pedikaki et al 2011) who assessed the impact of customer traffic on service trade performance. The study employed the explanatory study approach. The study used both quantitative and qualitative research methods to come up with the results. The research study was carried out on 34 formal clothing retail shops, 40 vendors operating in Main Street, and 150 customers conveniently selected in town. The research found out that street vending resulted in decrease of customer count for formal clothing retailers by 20% between 2013 and 2015.the massive engagement of street vending in Main Street of Gweru resulted in reduced financial performance of formal clothing retailers. The study also found out that there is a positive relationship between street vending and conversion rate. In other words, one percent change in street vending will automatically lead to a rise in financial performance of formal clothing retailers by 2%. The other main finding was that there is a negative relationship between street vending and average shopping cart of formal retailers. In conclusion the study established a relationship between street vending and financial performance of formal retailers. In light of this, the study recommended the construction of organised flea markets, retailers to engage in shopper marketing, continuous research and development, and relationship marketing. The study ended by calling for research studies in other regions of the world to assess the impact.